2014
DOI: 10.1093/nar/gku373
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C controls activation of the DNA integrity checkpoint

Abstract: The protein kinase C (PKC) superfamily plays key regulatory roles in numerous cellular processes. Saccharomyces cerevisiae contains a single PKC, Pkc1, whose main function is cell wall integrity maintenance. In this work, we connect the Pkc1 protein to the maintenance of genome integrity in response to genotoxic stresses. Pkc1 and its kinase activity are necessary for the phosphorylation of checkpoint kinase Rad53, histone H2A and Xrs2 protein after deoxyribonucleic acid (DNA) damage, indicating that Pkc1 is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 71 publications
0
34
1
1
Order By: Relevance
“…In S . cerevisiae , Pkc1 controls multiple cellular processes in addition to the downstream MAP kinase cascade, including activation of DNA integrity checkpoints [42], microtubule functions [43], glycerol metabolism [44, 45], as well as organization of the actin cytoskeleton [46]. In C .…”
Section: Discussionmentioning
confidence: 99%
“…In S . cerevisiae , Pkc1 controls multiple cellular processes in addition to the downstream MAP kinase cascade, including activation of DNA integrity checkpoints [42], microtubule functions [43], glycerol metabolism [44, 45], as well as organization of the actin cytoskeleton [46]. In C .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this proposed role for PKCδ fits well with the evidence that PKCδ functions as an apical regulator of apoptosis. Some studies place PKCδ upstream of the DNA damage sensors, DNA-dependent protein kinase, and ataxia telangiectasia mutated (ATM) and suggest a role for PKCδ in their activation in response to DNA damage (Bharti et al, 1998; Arango et al, 2012; Soriano-Carot, Quilis, Bano, & Igual, 2014). PKCδ has also been shown to function downstream of ATM activation (Li et al, 2004; LaGory, Sitailo, & Denning, 2010).…”
Section: Biological Functions Of Pkcδmentioning
confidence: 99%
“…In this regard, PKCδ-dependent regulation of MAPK pathways (Efimova, Broome, & Eckert, 2004; Murriel et al, 2004; Blank et al, 2013), PI3K-Akt (Murriel et al, 2004), signal transducer and activator of transcription-1 (STAT-1) (DeVries, Kalkofen, Matassa, & Reyland, 2004), and NFκB (Ren et al, 2014; Dong et al, 2015) has been shown in many contexts. In a second scenario, PKCδ could directly regulate the DNA damage response and cell cycle arrest mechanisms, as discussed above, pushing a cell toward initiation of apoptotic pathways (Bharti et al, 1998; Yoshida et al, 2003; LaGory et al, 2010; Arango et al, 2012; Soriano-Carot et al, 2014). Evidence supports both scenarios, raising the possibility that PKCδ, or a PKCδ effector, may have a dual function in cell survival and cell death.…”
Section: Biological Functions Of Pkcδmentioning
confidence: 99%
“…Thus, linking these protein targets to brain developmental effects induced by BafA1 or Rapa seems plausible. Other proteins, like BMPs, TNC, PKC, and CST3 could potentially and indirectly aid either of the two drugs in having impacts on the cellular processes shown in Figure 3a by their roles in astrocytic maturation and mitogenesis, migration, tumor invasion, and controlling DNA checkpoints required for maintaining genomic integrity [45,[47][48][49].…”
Section: Implications Of Bafa1/rapa-dysregulated Intracellular Astrocmentioning
confidence: 99%